Environment, agroforestry & livestock management / (Acc. 4553) - Kundu, S. S.; Pathak, P. S. (Lucknow : International Book Distributing Co., 2008)
Contributed articles with reference to India.
Keywords: Agroforestry; Range management; Livestock; Natural resources